2011
DOI: 10.2500/ajra.2011.25.3599
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Allergic Rhinitis Caused by Grass Pollen or House-dust Mites in Spain

Abstract: The duration of AR in patients attended for the first time by specialists is long and, in general, the disease does not improve over time and is often not well controlled with pharmacologic interventions. Less than one-half of patients receive allergen-specific immunotherapy that is more often prescribed in HDM allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…32, No. 4,2015 with persistent allergic rhinitis, but our study revealed that this risk is correlated with allergic rhinitis duration and sensitization to house dust mites, similar to other studies (3,28,29). However, there is no correlation between baseline cytokine levels and the risk of asthma after 1.5 years.…”
Section: Discussionsupporting
confidence: 75%
“…32, No. 4,2015 with persistent allergic rhinitis, but our study revealed that this risk is correlated with allergic rhinitis duration and sensitization to house dust mites, similar to other studies (3,28,29). However, there is no correlation between baseline cytokine levels and the risk of asthma after 1.5 years.…”
Section: Discussionsupporting
confidence: 75%
“…To our knowledge, no other pediatric study has examined similar North‐South gradients at country level in Europe and linked to markers of disease severity or comorbidities. Geographic differences of sensitization patterns in patients with respiratory allergies have been reported in Spain or France , but they focused on coast vs. continental areas rather than a North‐South gradient. Given its geographic characteristic (a country elongated from North to South), Italy can reproduce better than other countries the North‐South gradients typically observed, on a wider scale, at European level.…”
Section: Discussionmentioning
confidence: 99%
“…18 The discrepancy can perhaps be explained by the fact that 73% of the patients were recruited between January and May when the period of greatest severity of symptoms of allergic rhinitis due to HDM, including nasal congestion, is between October and December. 19 Pharmacologic symptomatic treatment was indicated in almost all patients included in the study and agents were used in combination. Up to 92% of the patients were prescribed oral second-generation antihistamines even though there is still some debate concerning the efficacy of these agents.…”
Section: Discussionmentioning
confidence: 99%